Kognisi Sosial Media dan Representasi Aktor Sosial dalam Pemberitaan Kekerasan terhadap Jurnalis - Siti Noorjannah Moegis; Gallant Karunia Assidik (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study aims to examine the dimensions of social cognition in news coverage of violence against journalists on Tempo.co and Kompas.com using Teun A. Van Dijk’s Critical Discourse Analysis (CDA) model, integrated with Van Leeuwen’s (1996) framework of social actor representation as a form of theoretical triangulation. The data consist of 22 news articles—11 from Tempo.co and 11 from Kompas.com—selected purposively from the period 2017–2026, with the units of analysis including word choice, narrative structure, patterns of source selection, and direct quotations. The results of the analysis reveal two fundamentally different mental models: Tempo.co operates from a mental model of state violence as an attack on democracy, featuring institutional categorization and arguments regarding historical impunity, whereas Kompas.com operates from a mental model of violence as an event that must be verified in a balanced manner, featuring personal nominations and presumed epistemic modalities. These differences are structural in nature, operating consistently through word choice, source selection patterns, and quotation structures. This study contributes to the development of AWK methodology through the operationalization of Van Dijk’s social cognition based on verified textual evidence, as well as a multi-year comparative design that has never before been applied to two major Indonesian media institutions.